Chemistry for Foundation Studies (Level 1) - Jamaudin, Rosmaya; Parmin, Siti Ruziani; Husain, Suhaili; Adan, Daliza (Cengage Learning, 2024)
Chemistry for foundation studies (level 1) is a book designed specifically for pre-university level students taking chemistry at local universities. It consists of complete notes covering seven chapters of general chemistry. Important principles and concepts are presented clearly and in simple ways to assist students in gaining clear understanding by using four colored illustrations when necessary. Learning objectives are provided at the start of each chapter to inform the students of the principles, concepts and skills they should learn. Solutions for each example show students the steps required in solving the problems. Exercises are provided following each example to give immediate practice to strengthen the learning of the concepts. Additional exercises are supplied at the end of each chapter, not only to reinforce the learning concepts but also to enhance problem-solving skills. We hope that this book will help students to gain sufficient chemistry knowledge to fulfill the requirements of any university courses.